Biodiversity of Enterobacteriaceae on masin (fermented sauce) from Sumbawa, West Nusa Tenggara, Indonesia - Baso Manguntungi; Dinar Saputri; Chairul Afgani; Apon Mustopa; Fatimah; Amirin Kusmiran (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Manguntungi B, Saputri DS, Afgani CA, Mustopa AZ, Fatimah, Kusmiran A. 2020. Biodiversity of Enterobacteriaceae on masin (fermented sauce) from Sumbawa, West Nusa Tenggara, Indonesia. Biodiversitas 21: 1001-1006. Masin is fermented sauce originating from Sumbawa, West Nusa Tenggara which is made from raw shrimp with the addition of tamarind, salt, and fingerroot (Boesenbergia pandurata) flower. The study aimed to determine the biodiversity of pathogenic bacteria, especially Enterobacteriaceae family in Masin. The methods used in this study were isolation of bacteria using MRS media with modified NaCl concentration (1-12%) and molecular identification by using PCR-RAPD (randomly amplified polymorphic DNA) analysis and 16S ribosomal RNA-based sequencing analysis. The characteristics of bacteria that were successfully isolated on media with various concentrations of salt were round, milky white, and formed a flat edge with convex elevation in each colony. The highest bacterial population was 29.65 x 106 CFU/g in MRS + NaCl 7% treatment. From 48 selected isolates that morphologically close to Enterobacteriaceae family, 5 isolates were chosen for sequencing analysis. Based on the phylogenetic analyses, isolate 01 had a close kinship with Leclercia adecarboxylata, isolate 11 had a close kinship with Citrobacter freundii, isolate 33 had a close kinship with Enterobacter cloacae, isolate 40 had a close kinship with Pantoea agglomerans and isolate 46 had a close kinship with Enterobacter ludwigii.